The Importance of Motivation in Learning A Foreign Language - Li Svetlana Pavlovna (Genius Publishing Group, 2022)
This article discusses the importance of motivation in learning a foreign language. It studied the problem of learning motivation as the problem of transforming the object of learning into the subject of learning activity. The stimulating effect of external motivation on the learning process can be quite strong, so it is important to build it in such a way that students at each stage feel progress towards the goal.
Keywords: motivation; culture; personality; formation